Hooked on fat: the role of lipid synthesis in cancer metabolism and tumour development - Franziska Baenke; Barrie Peck; Heike Miess; Almut Schulze (The Company of Biologists, 2013)
An increased rate of lipid synthesis in cancerous tissues has long been recognised as an important aspect of the rewired metabolism of transformed cells. However, the contribution of lipids to cellular transformation, tumour development and tumour progression, as well as their potential role in facilitating the spread of cancerous cells to secondary sites, are not yet fully understood. In this article, we review the recent findings that support the importance of lipid synthesis and metabolism in tumorigenesis. Specifically, we explore the role of aberrant lipid biosynthesis in cancer cell migration and invasion, and in the induction of tumour angiogenesis. These processes are crucial for the dissemination of tumour cells and formation of metastases, which constitute the main cause of cancer mortality.